Tingkat Pengetahuan Berhubungan dengan Usaha Mencari Bantuan Terkait Kegawatdaruratan - Teguh Santoso; Lukman Nulhakim Abdul Kader; Erika Nurwidiyanti (NERS Jurnal Keperawatan)
Background: Emergencies are circumstances that require immediate action or require first aid. The most common emergency is a traffic accident which can cause injuries. The death toll from traffic accidents is 30,000 people per year and the morbidity is 20,000 people per year. Efforts are being made to reduce the number of mortality and morbidity that is issued by PSC 119 emergency medical services.